2007
DOI: 10.1093/annonc/mdl426
|View full text |Cite
|
Sign up to set email alerts
|

Primary therapy for adults with T-cell lymphoblastic lymphoma with hematopoietic stem-cell transplantation results in favorable outcomes

Abstract: A treatment strategy for adults with chemosensitive T-LBL that includes planned consolidation with SCT in first response produces favorable long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 17 publications
(17 reference statements)
2
42
1
Order By: Relevance
“…LL is rare in adult patients, the most recent prospective series dealing with 27-34 total patients (a figure comparable to our study), with only a single study from Germany including exceptionally 45 patients [8,9,19,20]. In the NILG program, induction chemotherapy was integrated with early mediastinal irradiation in patients with suboptimal tumor regression, whereas the molecular analysis of MRD was used for the first time in adult LL to decide between SCT and standard maintenance for postinduction therapy.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…LL is rare in adult patients, the most recent prospective series dealing with 27-34 total patients (a figure comparable to our study), with only a single study from Germany including exceptionally 45 patients [8,9,19,20]. In the NILG program, induction chemotherapy was integrated with early mediastinal irradiation in patients with suboptimal tumor regression, whereas the molecular analysis of MRD was used for the first time in adult LL to decide between SCT and standard maintenance for postinduction therapy.…”
Section: Discussionsupporting
confidence: 75%
“…The protocol was designed such that patients who were found to be positive for MRD were switched from standard chemotherapy to allogeneic SCT (or alternatively to HD therapy with autologous stem cell support). Past studies have confirmed the therapeutic efficacy of SCT in adults with LL [19,29,30], with survival rates of 55-72%, which almost overlap with the best results obtained with chemotherapy. Although allogeneic SCT might no longer be a routine choice in the current era of improved chemotherapy results [3,8,9], it remains the most effective treatment modality for acute lymphoid malignancies beyond CR1 [31].…”
Section: Discussionmentioning
confidence: 79%
“…23 Palliative regimens included observation, radiation, immunotherapy alone, and non-anthracycline-based chemotherapy. High-dose chemotherapy included ALL-type regimens (n ϭ 2) 24 and high-dose chemo-radiotherapy followed by hematopoietic stem cell transplantation (autologous n ϭ 3; and allogeneic n ϭ 1). Ethical approval to perform this retrospective study was granted by the University of British Columbia-British Columbia Cancer Agency Research Ethics Board and is in accordance with the Declaration of Helsinki (REB no.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33] Virus-Associated Lymphomas Two lymphomas seen in adults are known to be causally associated with specific viruses. Adult T-cell leukemia/lymphoma is a T-cell lymphoma that is caused by human T-cell lymphotropic virus type 1.…”
Section: Leukemia-like Lymphomasmentioning
confidence: 99%